How recurrent floods create inequality in livelihood improvement through education - Leon Vin; Akiyuki Kawasaki; Sutee Anantsuksomsri (Humanities & Social Sciences Communications)
Abstract Education is a powerful tool against poverty and inequality, yet its potential is undermined by floods. While floods do not affect the population equally, previous studies have ignored the chronic impact of recurrent flooding on education across different economic strata, thereby overlooking the effect of inequality. Our study investigates this dynamic along Thailand’s Chao Phraya River, exploring a novel research topic: “How recurrent floods create inequality in livelihood improvement through education”. Using qualitative methods, we conducted in-depth household interviews lasting 1.5 to 2 h per household. These interviews revealed stark differences in educational experiences between rich and poor, whether these people were flood-affected or not. Even when exposed to the same flood conditions, wealthier households tend to maintain stability while poorer families face severe disruptions that limit their ability to support their children’s education, thereby perpetuating the poverty cycle. Non-flooded poor often exhibit optimism and focus on livelihood upward growth, whereas the flooded poor may face a daily struggle to survive, leaving little time and opportunity for future planning. Meanwhile, affluent families, regardless of flooding, continue to accumulate wealth and pass advantages to their children, further widening economic inequality. Our findings highlight how recurrent flooding not only entrenches poverty but also exacerbates disparities by disrupting education. This underscores the important, and new, notion that to elevate poverty and reduce inequality in flood-prone developing countries, education alone is insufficient.